ANALISIS PERAN PEMERINTAH DALAM MEMBANGUN KEWIRAUSAHAAN DAN PENDAPATAN PER KAPITA DI SEMBILAN NEGARA ASEAN 2014-2018 - Hardjono, Muchammad Dafirino; Setyari, Ni Putu Wiwin (Buletin Studi Ekonomi; VOLUME.27.NO.2.TAHUN.2022, 2022)
GDP per capita can be used to see the welfare or standard of living of the average people in a country from year to year. GDP per capita can also show whether the development progress carried out by the government has been successful. This study aims to analyze the effect of the ease of doing business index and government effectiveness on GDP per capita mediated by entrepreneurship in nine ASEAN countries. This research was conducted by analyzing secondary data, the data were then analyzed using path analysis techniques. The results showed that the ease of doing business index and government effectiveness did not directly affect GDP per capita. The ease of doing business index and government effectiveness have a positive and significant effect on entrepreneurship. Entrepreneurship plays a role in mediating the effect of the ease of doing business index and government effectiveness on GDP per capita. These results mean that increasing the ease of doing business index and government effectiveness can indirectly increase GDP per capita through the increased entrepreneurship.